Challenges and Opportunities in Adopting Heutagogy in Formal School Environments - Haryadi, Rofiq Noorman; Kartomo, Thomas K.; Sunarsi, Denok (International Journal of Social Sciences, 2025)
Heutagogy, or learner-centered education focused on autonomy, has gained increasing attention as an innovative approach in 21st-century education. This approach emphasizes flexible learning, student autonomy, and the development of critical thinking and problem-solving skills. However, the implementation of heutagogy in formal school environments faces various challenges, such as resistance from both teachers and students to changes in teaching methods, limitations in technological infrastructure, and curricula still based on traditional instruction. On the other hand, the adoption of heutagogy also presents significant opportunities, including enhanced learning motivation, the development of lifelong learning skills, and better adaptation to technological advancements and labor market demands. This research employs a qualitative method with a case study approach, involving direct observation, in-depth interviews with teachers and students, as well as policy document analysis related to heutagogy. Data were collected from several formal schools that have started implementing this approach, at both secondary and upper levels. Data analysis was conducted using triangulation techniques to ensure the validity and reliability of the findings. The results indicate that collaboration among teachers, students, and school authorities, as well as the appropriate use of educational technology, can provide solutions to effectively integrate heutagogy into formal learning systems.